A qualitative exploration of university students’ perspectives on distance education in Jordan: An application of Moore’s theory of transactional distance - Al-Tammemi, Ala’a B.; Nheili, Rana; Jibuaku, Chiamaka H.; Al Tamimi, Dua’a; Aljaberi, Musheer A.; Khatatbeh, Moawiah; Barakat, Muna; Al-Maqableh, Hindya O.; Fakhouri, Hussam N. (Frontiers in Education, 2022)
The current study aimed at exploring university students’ perspectives on the emergency distance education strategy that was implemented during the COVID-19 crisis in Jordan, one of the countries in the Eastern Mediterranean Region. Utilizing a qualitative design supported by Moore’s theory of transactional distance, a total of 17 semi-structured interviews were conducted with university students of various study levels and disciplines. Data were inductively analyzed using thematic analysis as suggested by Braun and Clarke. Seven themes have emerged, including, (i) Students’ psychological response to the sudden transition in educational process, (ii) Students’ digital preparedness, equality, and digital communication, (iii) Students’ and teachers’ technical competencies and technostress, (iv) Student-student and student-teacher interpersonal communication, (v) Quality and quantity of learning materials, (vi) Students’ assignments, examinations, and non-reliable evaluation methods, and (vii) Opportunities with positive impact of distance learning. The study findings provide evidence that the sudden transition from traditional on-campus to online distance education was significantly challenging in many aspects and was not a pleasant experience for many participants. Various factors under the jurisdiction of academic institutions and decision-makers are considered main contributing factors to the students’ educational experiences amid the pandemic crisis. Therefore, better planning and more sustainable utilization of educational resources have paramount importance in providing a high-quality education. Additionally, more dedicated efforts in terms of equitable, reliable, and credible evaluation systems should be considered in Jordan’s distance education strategy.